Characteristic Tests of Bio-pellets Made of Calliandra Wood as a Renewable Alternative Fuel - Permatasari, Rosyida; Muthia Atikayanti; Elisanti Sugitha Ginting (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2022)
Calliandra wood is a kind of forest biomass located in Baturaden Adventure Forest (BAF). The availability of which is quite abundant, so it has such an outsized potential to be processed into biopellets. This study was aimed at creating biopellets made of Calliandra wood and assessing their calorific value and their proximate value, and doing the mechanical and the combustion tests. This wood was converted into bio-pellets by employing several processes such as the drying, crushing, and milling processes, as well as the process of a 60-mesh sifting and the process of printing the bio-pellets with a starch adhesive of 16% Calliandra wood powder mass. Based on the results of this study, it was found out that the characteristics of the Calliandra wood biopellets taken from BAF had met the standards recommended by SNI 8021:2014, namely that of an over 4000 cal/gr calorific value, 3.6 % maximum moisture content, 69.4% maximum volatile matter content, 0.95% maximum ash content and 26% minimum fixed carbon content. The tests found out that the maximum stress value was 2.5MPa. and 66gram Calliandra wood bio-pellet could boil 500 ml of water in 6.5 minutes. Therefore, the biopellets can highly effectively be used as an alternative fuel.